2021
DOI: 10.1038/s41598-020-80326-w
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced amniotic fluid stem cell secretome augments cardiomyocyte proliferation and enhances cardioprotective effects under hypoxic-ischemic conditions

Abstract: Secretome derived from human amniotic fluid stem cells (AFSC-S) is rich in soluble bioactive factors (SBF) and offers untapped therapeutic potential for regenerative medicine while avoiding putative cell-related complications. Characterization and optimal generation of AFSC-S remains challenging. We hypothesized that modulation of oxygen conditions during AFSC-S generation enriches SBF and confers enhanced regenerative and cardioprotective effects on cardiovascular cells. We collected secretome at 6-hourly int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…The rationale comes from studies demonstrating that systemic injection of hAFSC-conditioned medium can provide prompt cardioprotective effects, by decreasing infarct size and enhancing myocardial cell survival in a rat model of acute ischaemia-reperfusion injury [ 53 ]. Similar cardioprotective and stimulatory paracrine effects from the secretome of human amniotic fluid progenitors were also obtained by follow-up studies based on models of doxorubicin-induced cardiotoxicity both in vitro and in vivo [ 51 , 52 ] and from independent work in a myocardial ischemia-reperfusion (I/R) injury mouse model [ 78 ]. In particular, myocardial infarction (MI) can often lead to the onset of heart failure (HF), which afflicts up to 38 million people in the world [ 79 ].…”
Section: Evs From Human Amniotic Fluid Stem Cells As Promising Medicinal Therapeuticsmentioning
confidence: 59%
“…The rationale comes from studies demonstrating that systemic injection of hAFSC-conditioned medium can provide prompt cardioprotective effects, by decreasing infarct size and enhancing myocardial cell survival in a rat model of acute ischaemia-reperfusion injury [ 53 ]. Similar cardioprotective and stimulatory paracrine effects from the secretome of human amniotic fluid progenitors were also obtained by follow-up studies based on models of doxorubicin-induced cardiotoxicity both in vitro and in vivo [ 51 , 52 ] and from independent work in a myocardial ischemia-reperfusion (I/R) injury mouse model [ 78 ]. In particular, myocardial infarction (MI) can often lead to the onset of heart failure (HF), which afflicts up to 38 million people in the world [ 79 ].…”
Section: Evs From Human Amniotic Fluid Stem Cells As Promising Medicinal Therapeuticsmentioning
confidence: 59%
“…For this reason, we further tested the secretome of hAFSCs upon neural differentiation induction with this particular chemical combination. Recent studies by other authors (Kukumberg et al, 2021) showed that hAFSCs under hypoxic conditions, in comparison to normoxic state, secrete larger quantities of growth factors such as BDNF and VEGF. Results of our ELISA analysis revealed that secretion of BDNF and VEGF proteins is also increased after the induction of neurogenic differentiation by a comparable degree in hAFSCs from both normal and pathological pregnancies (Figures 8C,D).…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, a growing body of research confirms the positive effects of hypoxic cultivations on MSCs isolated from different tissues [ 73 , 74 , 75 , 76 ]. It was demonstrated that expansion in low oxygen concentrations or priming with hypoxia increases the expression of growth factors [ 77 ], pro‐angiogenic and anti‐inflammatory factors [ 78 ], the biological activity of extracellular vesicles [ 76 ], proliferation rates [ 73 , 79 ] and self‐renewal capacity [ 80 ] of MSCs from different sources. Using adipose tissue‐derived MSCs which were modified with genetically encoded hypoxia sensors, it was demonstrated that HIF‐1a is stabilized in these cells starting from 7.5% O 2 in incubator overlay [ 81 ].…”
Section: Influence and Importance Of Hypoxic Cultivation Conditionsmentioning
confidence: 99%